Assessing Temporal Changes in Microbial Communities in Hyalomma dromedarii Collected From Camels in the UAE Using High-Throughput Sequencing - Perveen, Nighat; Muzaffar, Sabir Bin; Vijayan, Ranjit; Al-Deeb, Mohammad Ali (Frontiers in Veterinary Science, 2022)
Ticks (Acari) are ectoparasites of animals that harbor communities of microbes of importance to animal and human health. Microbial communities associated with ticks exhibit temporal patterns of variation in their composition, with different genera dominating at different times of the year. In this study, molecular tools were used to assess the composition of the microbial communities associated with Hyalomma dromdarii. Adult ticks were collected on a monthly basis for one year from 25 camels in the UAE. A total of 12 DNA pools were prepared (one pool for each month). We monitored the microbiota of ticks using high-throughput sequencing of the V3-V4 region of the bacterial 16S rRNA gene. A total 614 operational taxonomic units were produced through de novo clustering, and belonged to 17 phyla, 30 classes, 46 orders, 118 families, and 222 genera. Fifteen bacterial families were found to be the most abundant. The dominant bacterial communities associated with H. dromedarii belonged to the genera Staphylococcus, Bacillus, Francisella and Corynebacterium, which were reported with high relative abundance from all months. No significant correlation occurred between the abundance of microbial families or genera in H. dromedarii ticks and the ambient temperature. Our findings revealed for the first time in the UAE, temporal fluctuations of microbial communities in H. dromedarii ticks and provided key insights on the interaction between different microbial groups. Moreover, our results contribute to the current understanding of disease development and allow more investigations for potentially pathogenic microbiota.